Outpatient-based buprenorphine-assisted opioid withdrawal management: A preliminary prospective observational study - Avinash Jhajharia; Priyanka Saha; Piyali Mandal; Atul Ambekar (Indian Journal of Psychiatry)
Background: Indian guidelines mention the use of buprenorphine in opioid withdrawal in both outpatient and inpatient setting. Aim: This is the first study aiming at assessing the feasibility aspects of outpatient-based buprenorphine-assisted opioid withdrawal treatment for opioid dependence. Methods: In this prospective observational study, 30 men with opioid dependence, planned for outpatient-based withdrawal management, were recruited by purposive sampling and were assessed at baseline, 2, 4, and 12 weeks using validated tools. Abstinence was validated by a urine toxicology screen. Results: The median age of the sample was 24 (21.75–28.0) years. About 67% retained in treatment with a treatment perception score of 4.1 (4.0–4.4) and a significant reduction of craving and withdrawal scores. More than 80% were abstinent at 12 weeks. Conclusion: The study findings suggest that outpatient-based buprenorphine-assisted acute opioid withdrawal management is a feasible and acceptable treatment. Considering the relatively few inpatient addiction treatment settings, the findings are promising.